Management of English Language Learning Process for Children and Adolescent through Distance Learning Program at Homeschooling - Musdalifah Ifah Rahman (Universitas Muhammadiyah Enrekang, 2020)
The research aimed to illustrate how distance learning programs can be organized or administered at